Cultural Action and the Defense of Public Life - Viganó, Suzana Schmidt (Revista Brasileira de Estudos da Presença, 2022)
The article proposes a reflection on the consecrated idea of cultural action, which intends to revisit the notion of public life. Cultural action is thus understood in its historical development and it is questioned in its potentiality as an action in times of political and democratic crisis. From the dialogue with Political Philosophy and from the analysis of artistic and pedagogical practices, besides the public intervention of São Paulo artists, we reflect on the perspectives of cultural action in the current historical moment, focusing on it as an expression of the public sphere and political participation, broadening the spheres of sharing the sensitive field and re-singularizing the existential universes.